Outcome of Radical Cystectomy With Urinary Diversion at Nicrh, Bangladesh (Bangladesh Journal of Urology, 2020)
Introduction: Radical Cystectomy (RC) is an effective surgical procedure for muscle invasive bladder cancer ( MIBC). 5 years disease free survival after RCs are PT2 - 81%, PT3a – 68%, PT3b – 47%, PT4a – 44% respectively, Stein et al, 2001[1]. In this study early surgical & oncological outcome have been assessed.Patients & methods: A total of 24(N) patients underwent radical cystectomy with urinary diversion between December 2013 to June 2016. Age ranges from 41-69 years. Indications were T2HG for twenty cases and T1HG for four cases. Among the T1 tumours, one had early recurrence, one had numerous tumours and two had multiple tumours with concomitant CIS. Urinary diversion methods were: Orthotopic Ileal neobladder-1, Ileal conduit-20, Cuteneous Ureterostomy -3 (2 due to unhealthy mesentry with gut, 1 single kidney with poor general condition), For uretero-Ileal anaestomosis we used Bricker method in all cases.Result: Mean OR time was 3:45 hours, blood loss average 350 ml, hospital stay after operation 9 days, enlarged pelvic lymph nodes were found in two cases. In follow up we found,stomal stenosis of cutaneous ureterostomy in 1 out of 3 cases, Ileal conduit prolapse with para-stomal hernia in 1 out of 20 cases, stenosis at uretero-Ileal anastomosis in 1 pt. .Distant recurrence occurred in two cases, one in Lt. Supraclavicular LN and another in sacrum near SI joint. No local recurrence was found in any case.Conclusion: Our experience on RC and all the three types of UD are safe and effective for patient and encouraging for us.Bangladesh Journal of Urology, Vol. 21, No. 2, July 2018 p.62-65